Organic antibacterial modifications of high-viscosity glass ionomer cement for atraumatic restorative treatment: A review - Damodar Hegde; Baranya Shrikrishna Suprabha; Arathi Rao (Elsevier, 2024)
High viscosity glass ionomer cement (HVGIC) has been employed as a restorative material for Atraumatic Restorative Treatment (ART). As residual caries persist after caries removal in ART, the antibacterial activity of HVGIC gains importance. Organic and inorganic substances with antibacterial properties have been incorporated into HVGIC over the years, and their effects on the antibacterial and physical properties have been studied. The objective of this paper is to review the various alterations made to HVGIC using organic compounds, their effect on the antibacterial activity, and the physical properties of the cement. Various in vitro investigations have been conducted by adding antiseptics, antibiotics, and naturally occurring antibacterial substances. Most of these compounds render superior antibacterial properties to HVGIC, but higher concentrations affect physical properties in a dose-dependent manner. However, some naturally occurring antibacterial substances, such as chitosan, improve the physical properties of HVGIC, as they enhance cross-linking and polysalt bridging. There is potential for clinical benefits to be gained from the addition of organic antibacterial compounds to HVGIC. In-depth research is required to determine the optimum concentration at which the antibacterial effect is maximum without affecting the physical properties of the cement.